2014
DOI: 10.1007/s12010-014-0818-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modification of Protein A to Improve the Elution pH and Alkali Resistance in Affinity Chromatography

Abstract: Protein A of Staphylococcus aureus has been widely used as an affinity ligand for the purification of immunoglobulin. However, the low elution pH and the sensitivity to alkaline condition restricted the large-scale application of antibody purification. To overcome these disadvantages, the B domain was selected and mutated to Z domain and the recombinant Protein A was reconstructed by linking five Z domains. First, a section of six glycines was inserted into the second loop of Z domain, Z (6G). This increased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…To address the issue with CIP procedures, SpA was shown to have higher alkaline stability with a single mutation at position 29, with G29W being the most stable (142). Two further mutations N23T and F30A to the SpA Z domain resulted in a higher alkaline resistance when compared to wild type (143). SpA Z domain was also engineered to include six glycine residues on the second loop, which resulted in an increase in the elution pH (143).…”
Section: Superantigen Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address the issue with CIP procedures, SpA was shown to have higher alkaline stability with a single mutation at position 29, with G29W being the most stable (142). Two further mutations N23T and F30A to the SpA Z domain resulted in a higher alkaline resistance when compared to wild type (143). SpA Z domain was also engineered to include six glycine residues on the second loop, which resulted in an increase in the elution pH (143).…”
Section: Superantigen Applicationsmentioning
confidence: 99%
“…Two further mutations N23T and F30A to the SpA Z domain resulted in a higher alkaline resistance when compared to wild type (143). SpA Z domain was also engineered to include six glycine residues on the second loop, which resulted in an increase in the elution pH (143). Wild type SpA is less susceptible to extreme alkaline conditions, with a halflife of 16 h (141) compared to SpG, which has a half-life of under 10 mins (144).…”
Section: Superantigen Applicationsmentioning
confidence: 99%
“…To address the issue with CIP procedures, SpA was shown to have higher alkaline stability with a single mutation at position 29, with G29W being the most stable [138]. Two further mutations N23T and F30A to the SpA Z domain resulted in a higher alkaline resistance when compared to wild type [139]. SpA Z domain was also engineered to include six glycine residues on the second loop, which resulted in an increase in the elution pH [139].…”
Section: Industrialmentioning
confidence: 99%
“…Two further mutations N23T and F30A to the SpA Z domain resulted in a higher alkaline resistance when compared to wild type [139]. SpA Z domain was also engineered to include six glycine residues on the second loop, which resulted in an increase in the elution pH [139]. Wild type SpA is less susceptible to extreme alkaline conditions, with a half-life of 16 h [137] than SpG, which has a half-life of under 10 mins [140].…”
Section: Industrialmentioning
confidence: 99%
“…Using a destabilized variant of the Z-domain which does not bind the Fc fragment as a template, Hober and co-workers showed that a N23T mutation increased chemical resistance to withstand cleaning-in-place protocols which is a critical parameter for biological affinity reagents [44]. More recently, Xia et al showed thatthe addition of six glycines in loop 2 of the Z-domain along with mutations in residues N29T and F30A greatly increased alkaline resistance to sodium hydroxide extending cleaning in place (CIP) up to 2M in 1h and allowed recovery of antibodies at milder pH [45]. The approach that conferred the Z-domain alkaline resistance was tested towards the C-domain of SpA.…”
Section: Improving the Performance Of A Natural Affinity Ligandmentioning
confidence: 99%